Análise do desenvolvimento de sementes de mamoeiros (Carica papaya L.) infectados com Papaya ringspot vírus e Papaya meleira vírus - Salgado, Raquel Pereira Passos (2015)
The papaya (Carica papaya L.) is a fruit tree very important for the State of Espírito Santo, which is the second largest producer and the largest exporter of papaya in Brazil. However, the diseases papaya sticky desease (or meleira) and mosaic of papaya, caused, respectively, by Papaya meleira virus (PMeV) and Papaya ringspot virus-P (PRSV-P), are the main limiting factors. The seeds of Carica papaya are intermediate, for tolerance to desiccation, its reserve tissue is the endosperm, has asynchronous germination due to the presence of inhibitors in the sarcotesta region. It is known that viral transmission by seeds is a very important route for the spread of PMeV, and PRSV-P is not typically transmitted through this route. This study aims to evaluate if there is interference of PMeV and PRSV-P on the germination of seeds from infected plants. This research found that the PMeV causes the reduction of seeds biomass, germination rate, growth and biomass of the plants, and damage in the surface structure of the embryos. The PRSV-P virus demonstrated does not compromise any of the parameters. In conclusion, PMeV virus affect the formation and development of the seeds of infected papaya cv. Golden plants, and the PRSV-P virus does not cause any damage to seed as the PMeV virus does